PROSES KERJA MESIN ROTARY DRYER PADA PEMBUATAN PUPUK ORGANIK GRANUL DI PT. PETROSIDA GRESIK SUMEDANG - Ajat Maulana Safrudin (PROCEEDING STIMA)
Drying is a way to remove or partially remove water from a material by evaporation through the use of heat energy. The water content is reduced to some extent. Drying in the industry usually uses one of the tools by using a rotary dryer. At PT. Petrosida Gresik Sumedang on the manufacture of organic fertilizer granule drying process using the rotary dryer.The rotary dryer works by flowing hot streams in contact with the material to be dried. Rotary dryer dryers are used to dry powder-shaped materials, granules, large solid particle clumps. The drying of the rotary dryer is repeatedly rotated so that not only the top surface undergoes a drying process, but also on all parts of the top and bottom alternately so that drying using the tool is more evenly distributed and more shrinkage.